Preparation method of biodegradable flexible radiation refrigeration film

The preparation of ethyl cellulose-based flexible radiation refrigeration films through electrospinning technology solves the problems of difficult to take into account the ultraviolet resistance, cooling performance and biodegradability of polymer-based radiation cooling materials, and achieves efficient and environmentally friendly passive radiation refrigeration effects during the day and naturally degrade in the environment.

CN119663539AActive Publication Date: 2025-03-21HARBIN INST OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510093276.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-21
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Existing polymer-based radiation-cooling materials cannot simultaneously possess excellent UV resistance, cooling performance and biodegradability, resulting in oxidation and yellowing of oxidation under long-term exposure to UV radiation, reducing cooling performance and increasing the risk of environmental pollution.

Method used

Ethyl cellulose-based flexible radiation refrigeration film is prepared through electrospinning technology, the concentration and process parameters of the spinning liquid are controlled, and fiber membranes with high reflectivity and good radiation are prepared to achieve biodegradable materials with good UV resistance and radiation refrigeration effects.

Benefits of technology

The solar reflectivity of 98.1% and 88.4% were achieved, which can effectively passive radiation refrigerate during the day. The solar reflectivity was almost unchanged after the 600-hour strong ultraviolet irradiation test, avoiding yellowing and part of it was naturally degraded in the soil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663539A_ABST
    Figure CN119663539A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a biodegradable flexible radiation refrigeration film, and relates to a preparation method of a radiation refrigeration film. The invention aims to solve the problem that an existing polymer radiation cooling material cannot have excellent ultraviolet resistance, cooling performance and biodegradation at the same time. The method comprises the following steps: 1, preparing a spinning solution; and 2, synthesizing nano-scale and micron-scale EC fibers by adopting electrostatic spinning. The method is used for preparing the biodegradable flexible radiation refrigeration film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a radiation refrigeration film. Background Art

[0002] The continuous consumption of fossil fuels has led to increasing greenhouse gas emissions, which in turn has caused the earth's temperature to rise. Cooling technology has become an urgent need in our daily lives and industrial production. However, traditional cooling technologies usually consume fossil fuels, which exacerbates the problem of global warming. Therefore, it has become particularly urgent to find new green and fuel-free cooling technologies. Passive daytime radiative cooling (PDRC) radiates excess heat from the earth's surface to the ultra-cool outer space (about 3K) through the 8-13 μm spectral range in the atmosphere, thereby passively cooling objects without consuming any energy. In recent years, this cooling method has received increasing attention as an environmentally friendly alternative to electric cooling to help mitigate global warming. This cooling technology has been used intentionally or unintentionally in multiple scenarios, including energy-saving buildings, dew collection, personal thermal management, photovoltaic cooling, refrigeration and storage, and power generation.

[0003] At present, PDRC materials usually adopt complex structures such as multilayers and pores composed of photonic crystals, polymers and dielectric polymers to enhance solar reflectivity and mid-infrared emissivity. However, photonic crystal-based PDRC materials are difficult to mass-produce due to their complex and expensive manufacturing processes. On the other hand, polymer-based PDRC materials are favored due to their low cost and simple manufacturing methods. However, many polymer-based radiative cooling materials have poor ultraviolet (UV) resistance, and long-term exposure to UV radiation will lead to oxidation, which in turn causes yellowing. In addition, the increased absorption of UV light will reduce the cooling performance, which limits the widespread application of polymer-based radiative cooling materials. By combining UV-resistant photonic crystals with polymers, the UV resistance of polymer-based radiative cooling materials can be improved. However, polymer-based radiative cooling materials with UV resistance are generally non-biodegradable, which aggravates the problem of environmental pollution. Summary of the invention

[0004] The present invention aims to solve the problem that existing polymer radiation cooling materials cannot simultaneously have excellent UV resistance, cooling performance and biodegradability, and further provide a method for preparing a biodegradable flexible radiation cooling film.

[0005] A method for preparing a biodegradable flexible radiation refrigeration film is carried out according to the following steps:

[0006] 1. Preparation of spinning solution:

[0007] dissolving ethyl cellulose in a solvent to obtain a spinning solution;

[0008] Second, synthesize nano- and micron-sized EC fibers by electrospinning;

[0009] Electrospinning is carried out under the conditions of voltage of 13kV to 15kV, injection speed of 0.03mm / min to 0.08mm / min, temperature of 20℃ to 30℃, humidity of 20% to 30%, inner diameter of syringe needle of 0.06mm to 0.25mm, distance between syringe needle and receiving spinner of 20cm to 25cm, translation speed of syringe needle of 400mm / min to 600mm / min and rotation speed of receiving spinner of 1r / min to 3r / min. Finally, the solvent is removed by drying to obtain a biodegradable flexible radiation refrigeration film.

[0010] The beneficial effects of the present invention are:

[0011] The present invention controls the concentration of spinning solution and process parameters to prepare a fiber membrane that can be highly reflective in the solar band, which can achieve performance comparable to or even better than that of a refrigeration membrane with added fillers. This fiber membrane prepared through structural design can maximize performance while reducing unnecessary filler addition, which is of great significance in terms of cost savings and maintaining the intrinsic properties of the material.

[0012] The biodegradable flexible radiation cooling film prepared by the present invention has the characteristics of anti-ultraviolet, good radiation cooling effect and natural degradation. In the atmospheric window, a solar reflectivity of 98.1% and an emissivity of 88.4% are achieved, which can effectively provide passive radiation cooling during the day. After 600 hours of strong ultraviolet irradiation test, the solar reflectivity of the EC film has almost no change. By comparing the optical images before and after ultraviolet irradiation and the CIE 1931 chromaticity diagram, it is found that the EC film does not turn yellow under ultraviolet irradiation. The biodegradable flexible radiation cooling film is placed in the soil, and the EC film is partially degraded. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The physical image, SEM image, and comparison of solar reflectivity and mid-infrared emissivity of the EC fiber membrane prepared in Example 1, a is the physical image, b is the SEM image, and c is the solar reflectivity and mid-infrared emissivity;

[0014] Figure 2 The solar reflectivity of the EC fiber membrane prepared in Example 1 under different UV irradiation times;

[0015] Figure 3 The CIE 1931 chromaticity diagram and optical image of the EC fiber membrane prepared in Example 1 without ultraviolet irradiation and after 600 hours of ultraviolet irradiation, a is the CIE 1931 chromaticity diagram without ultraviolet irradiation, b is the CIE 1931 chromaticity diagram after ultraviolet irradiation, c is the optical image without ultraviolet irradiation, and d is the optical image after ultraviolet irradiation;

[0016] Figure 4 The natural degradation test diagram of the EC fiber membrane and the PE membrane prepared in Example 1 and the scanning electron microscope diagram of the EC fiber membrane after natural degradation, a is the natural degradation test diagram, b is the scanning electron microscope diagram of the EC membrane after natural degradation;

[0017] Figure 5 Figure 1 is a cooling performance test diagram of the EC fiber membrane prepared in Example 1. a is a photo of the outdoor daytime radiation cooling test, b is a schematic diagram of the device structure for real-time monitoring of the daytime radiation cooling performance, c is the relationship between the temperature (T) and time during the test, and d is the temperature difference during the test (ΔT = T amb -T cooler ) and time. DETAILED DESCRIPTION

[0018] Specific implementation method 1: This implementation method is a method for preparing a biodegradable flexible radiation cooling film, which is carried out according to the following steps:

[0019] 1. Preparation of spinning solution:

[0020] dissolving ethyl cellulose in a solvent to obtain a spinning solution;

[0021] Second, synthesize nano- and micron-sized EC fibers by electrospinning;

[0022] Electrospinning is carried out under the conditions of voltage of 13kV to 15kV, injection speed of 0.03mm / min to 0.08mm / min, temperature of 20℃ to 30℃, humidity of 20% to 30%, inner diameter of syringe needle of 0.06mm to 0.25mm, distance between syringe needle and receiving spinner of 20cm to 25cm, translation speed of syringe needle of 400mm / min to 600mm / min and rotation speed of receiving spinner of 1r / min to 3r / min. Finally, the solvent is removed by drying to obtain a biodegradable flexible radiation refrigeration film.

[0023] The beneficial effects of this embodiment are:

[0024] This embodiment controls the concentration of the spinning solution and the process parameters to prepare a fiber membrane that can be highly reflective in the solar band, which can achieve performance comparable to or even better than that of a refrigeration membrane with added fillers. This fiber membrane prepared through structural design can maximize performance while reducing unnecessary filler additions, which is of great significance in terms of cost savings and maintaining the intrinsic properties of the material.

[0025] The biodegradable flexible radiation cooling film prepared in this embodiment has the characteristics of anti-ultraviolet, good radiation cooling effect and natural degradation. In the atmospheric window, a solar reflectivity of 98.1% and an emissivity of 88.4% are achieved, which can effectively provide passive radiation cooling during the day. After 600 hours of strong ultraviolet irradiation test, the solar reflectivity of the EC film has hardly changed. By comparing the optical images before and after ultraviolet irradiation and the CIE 1931 chromaticity diagram, it is found that the EC film does not turn yellow under ultraviolet irradiation. The biodegradable flexible radiation cooling film is placed in the soil, and the EC film is partially degraded.

[0026] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the solvent in step 1 is a mixed solvent of glacial acetic acid / anhydrous ethanol / pure water. The rest is the same as specific implementation method 1.

[0027] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the volume ratio of glacial acetic acid to anhydrous ethanol in the mixed solvent of glacial acetic acid / anhydrous ethanol / pure water is 7:(2-3); the volume ratio of glacial acetic acid to pure water in the mixed solvent of glacial acetic acid / anhydrous ethanol / pure water is 7:(1-2). Other aspects are the same as specific implementation method 1 or 2.

[0028] Specific embodiment 4: This embodiment is different from one of specific embodiments 1 to 3 in that the mass percentage of ethyl cellulose in the spinning solution in step 1 is 20% to 28%. The rest is the same as specific embodiment 3.

[0029] Specific embodiment 5: This embodiment is different from Specific embodiments 1 to 4 in that: the drying to remove the solvent in step 2 is specifically drying at room temperature for 12 hours to 24 hours. The rest is the same as Specific embodiments 1 to 4.

[0030] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the receiving spinner in step 2 is a rotating drum wrapped with aluminum foil. The rest is the same as specific embodiments 1 to 5.

[0031] Specific embodiment 7: This embodiment differs from Specific embodiments 1 to 6 in that the fiber diameter of the biodegradable flexible radiative cooling film prepared in step 2 is 0.10 μm to 1.3 μm, and the pore size is 0.20 μm to 2.5 μm. The rest is the same as Specific embodiments 1 to 6.

[0032] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the solvent in step one is a mixed solvent of glacial acetic acid / anhydrous ethanol / pure water; the volume ratio of glacial acetic acid to anhydrous ethanol in the mixed solvent of glacial acetic acid / anhydrous ethanol / pure water is 7:2; the volume ratio of glacial acetic acid to pure water in the mixed solvent of glacial acetic acid / anhydrous ethanol / pure water is 7:1. Other aspects are the same as specific embodiments one to seven.

[0033] Specific embodiment 9: This embodiment is different from Specific embodiments 1 to 8 in that the mass percentage of ethyl cellulose in the spinning solution in step 1 is 28%. Other aspects are the same as Specific embodiments 1 to 8.

[0034] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: in step 2, the electrospinning is performed under the conditions of voltage of 15 kV, injection speed of 0.06 mm / min, temperature of 25° C., humidity of 25%, inner diameter of syringe needle of 0.23 mm, distance between syringe needle and receiving spinner of 25 cm, translation speed of syringe needle of 500 mm / min, and rotation speed of receiving spinner of 2 r / min. The rest is the same as specific embodiments 1 to 9.

[0035] The following examples are used to verify the beneficial effects of the present invention:

[0036] Embodiment 1:

[0037] A method for preparing a biodegradable flexible radiation refrigeration film is carried out according to the following steps:

[0038] 1. Preparation of spinning solution:

[0039] dissolving ethyl cellulose in a solvent to obtain a spinning solution;

[0040] Second, synthesize nano- and micron-sized EC fibers by electrospinning;

[0041] Electrospinning was carried out under the conditions of voltage of 15 kV, injection speed of 0.06 mm / min, temperature of 25°C, humidity of 25%, inner diameter of syringe needle of 0.23 mm, distance between syringe needle and receiving spinner of 25 cm, translation speed of syringe needle of 500 mm / min and rotation speed of receiving spinner of 2 r / min. Finally, the solvent was removed by drying to obtain a biodegradable flexible radiation refrigeration film, i.e., EC fiber membrane.

[0042] The solvent described in step 1 is a mixed solvent of glacial acetic acid / anhydrous ethanol / pure water; the volume ratio of glacial acetic acid to anhydrous ethanol in the mixed solvent of glacial acetic acid / anhydrous ethanol / pure water is 7:2; the volume ratio of glacial acetic acid to pure water in the mixed solvent of glacial acetic acid / anhydrous ethanol / pure water is 7:1.

[0043] The mass percentage of ethyl cellulose in the spinning solution described in step 1 is 28%.

[0044] The drying to remove the solvent in step 2 is specifically drying at room temperature for 12 hours.

[0045] The receiving spinner in step 2 is a rotating drum wrapped with aluminum foil.

[0046] The fiber diameter of the biodegradable flexible radiation cooling film prepared in step 2 is 0.10 μm to 1.3 μm, and the pore size is 0.20 μm to 2.5 μm.

[0047] Figure 1 The physical image, SEM image, and solar reflectivity and mid-infrared emissivity comparison of the EC fiber membrane prepared in Example 1, a is the physical image, b is the SEM image, and c is the solar reflectivity and mid-infrared emissivity. As can be seen from the figure, the membrane formed by the fiber accumulation contains nano- and micron-sized fibers and pores, which can strongly scatter sunlight, thereby achieving passive radiation cooling during the day. The EC membrane achieves a solar reflectivity of 98.1% and an emissivity of 88.4% in the atmospheric window, which can effectively achieve passive radiation cooling during the day.

[0048] The EC fiber membrane prepared in Example 1 was subjected to a 600-hour strong ultraviolet (UV) irradiation test (0.7 kW·h - 1), which is equivalent to about 400 days of continuous outdoor exposure in Harbin. The test results are as follows Figure 2 and Figure 3 As shown;

[0049] Figure 2 The solar reflectivity of the EC fiber membrane prepared in Example 1 under different UV irradiation times. As shown in the figure, the solar reflectivity of the EC membrane has almost no change after 600 hours of strong UV irradiation test, as shown in Table 1:

[0050] Table 1

[0051] UV exposure time Solar reflectivity (%) 0h 98.05609 100h 98.08368 200h 98.21156 300h 98.53732 400h 98.19011 500h 98.12102 600h 98.05698

[0052] Figure 3 CIE1931 chromaticity diagram and optical image of the EC fiber membrane prepared in Example 1 before and after 600 hours of ultraviolet irradiation, a is the CIE 1931 chromaticity diagram without ultraviolet irradiation, b is the CIE 1931 chromaticity diagram after ultraviolet irradiation, c is the optical image without ultraviolet irradiation, d is the optical image after ultraviolet irradiation; and the scale in the optical image is 1 cm; as can be seen from the figure, by comparing the optical image and the CIE 1931 chromaticity diagram before and after ultraviolet irradiation, it is found that the EC membrane does not turn yellow under ultraviolet irradiation.

[0053] The EC fiber membrane and polyethylene nanomembrane (PE membrane) prepared in Example 1 were placed in soil respectively to test natural degradation. The test time was from April 2, 2024 to November 25, 2024. Figure 4 The natural degradation test diagram of the EC fiber membrane and PE membrane prepared in Example 1 and the scanning electron microscope diagram of the EC fiber membrane after natural degradation, a is the natural degradation test diagram, and b is the scanning electron microscope diagram of the EC membrane after natural degradation. It can be seen from Figure a that after about 8 months, the EC fiber membrane is partially degraded in the soil, while the control PE membrane still maintains its complete morphology and structure. It can be seen from Figure b that the fiber structure at the edge of the membrane has disappeared and converted into fine particles. As a natural cellulose derivative, ethyl cellulose still has good biodegradability in nature. The edge of the EC membrane is more easily exposed to environmental factors such as moisture and oxygen, so it degrades faster, while the surface structure of the membrane is relatively stable, resulting in slower degradation.

[0054] Real-time monitoring of daytime radiation cooling performance: The equipment is mainly composed of a top covering PE film for shielding heat convection, surrounding insulation foam, an aluminum foil covering layer (for isolating ambient heat), a thermocouple and a temperature signal conversion module, and is equipped with a thermocouple to monitor the sample temperature in real time ( Figure 5 a and 5b). Six identical rectangular grooves (4 cm × 4 cm × 2 cm) were prepared on the top of the device to place the test samples (EC film, black carbon fiber, black carbon fiber covered by EC film and white paper) (4 cm × 4 cm) and thermocouples. During the outdoor test, the solar radiation power was measured using a solar radiometer (TES1333R, TES Electrical and Electronics Co., Ltd., China). The ambient humidity and wind speed can be read by the hygrometer and anemometer. Real-time temperature data were collected using a data logging thermometer with thermocouples (EX4000, Aeon (Shenzhen) Technology Co., Ltd., China). The device was placed on a rack on the roof to reduce heat convection from the ground; the test location was Harbin Institute of Technology (May 23, 2024, UTC+8, sunny to cloudy weather), and the ambient cooling performance of the EC film under direct sunlight in Harbin, China (45°43′49″N, 126°38′11″E, 128 m above sea level) was studied. Figure 5 Figure 1 is a cooling performance test diagram of the EC fiber membrane prepared in Example 1. a is a photo of the outdoor daytime radiation cooling test, b is a schematic diagram of the device structure for real-time monitoring of the daytime radiation cooling performance, c is the relationship between the temperature (T) and time during the test, and d is the temperature difference during the test (ΔT = T amb -T cooler ) and time; Field tests show that in a dry and sunny environment (relative humidity is about 20%, solar radiation is greater than 600W / m 2 , the peak value is about 961W / m 2), from 12:00 to 13:00, when the solar radiation was strong, the ambient temperature was 35.6℃, the temperature of the black carbon fiber reached 65.3℃, and the temperature of the carbon fiber covered by the EC film remained at 25.2℃, and the actual temperature dropped by 40.1℃, proving its cooling performance in actual situations ( Figure 5 c). Compared with the ambient temperature (35.6°C), the EC film (25.2°C) achieved a temperature drop of about 10.4°C (ΔT = T amb -T cooler , where T amb is the ambient temperature, T cooler is the cooling temperature of the cooling film)( Figure 5 d), while the actual temperature drop of the white paper is about 5.2°C, which is much lower than the cooling effect of the EC membrane, further proving the excellent cooling performance of the EC membrane.

[0055] According to the GB / T 16491-2022 test standard, the mechanical properties of the EC fiber membrane prepared in Example 1 were tested, and the Young's modulus of the EC fiber membrane was measured to be 10.1 MPa.

Claims

1. A method for preparing a biodegradable flexible radiation cooling film, characterized in that It is carried out in the following steps:

1. Preparation of spinning solution: dissolving ethyl cellulose in a solvent to obtain a spinning solution; Second, synthesize nano- and micron-sized EC fibers by electrospinning; Electrospinning is carried out under the conditions of voltage of 13kV to 15kV, injection speed of 0.03mm / min to 0.08mm / min, temperature of 20℃ to 30℃, humidity of 20% to 30%, inner diameter of syringe needle of 0.06mm to 0.25mm, distance between syringe needle and receiving spinner of 20cm to 25cm, translation speed of syringe needle of 400mm / min to 600mm / min and rotation speed of receiving spinner of 1r / min to 3r / min. Finally, the solvent is removed by drying to obtain a biodegradable flexible radiation refrigeration film.

2. The method for preparing a biodegradable flexible radiative cooling film according to claim 1, characterized in that The solvent described in step 1 is a mixed solvent of glacial acetic acid / anhydrous ethanol / pure water.

3. The method for preparing a biodegradable flexible radiation cooling film according to claim 2, characterized in that The volume ratio of glacial acetic acid to anhydrous ethanol in the mixed solvent of glacial acetic acid / anhydrous ethanol / pure water is 7:(2-3); the volume ratio of glacial acetic acid to pure water in the mixed solvent of glacial acetic acid / anhydrous ethanol / pure water is 7:(1-2).

4. The method for preparing a biodegradable flexible radiation cooling film according to claim 1, characterized in that The mass percentage of ethyl cellulose in the spinning solution described in step 1 is 20% to 28%.

5. The method for preparing a biodegradable flexible radiation cooling film according to claim 1, characterized in that The drying to remove the solvent in step 2 specifically involves drying at room temperature for 12 h to 24 h.

6. The method for preparing a biodegradable flexible radiation cooling film according to claim 1, characterized in that The receiving spinner in step 2 is a rotating drum wrapped with aluminum foil.

7. The method for preparing a biodegradable flexible radiative cooling film according to claim 1, characterized in that The fiber diameter of the biodegradable flexible radiation cooling film prepared in step 2 is 0.10 μm to 1.3 μm, and the pore size is 0.20 μm to 2.5 μm.

8. The method for preparing a biodegradable flexible radiation cooling film according to claim 1, characterized in that The solvent described in step 1 is a mixed solvent of glacial acetic acid / anhydrous ethanol / pure water; the volume ratio of glacial acetic acid to anhydrous ethanol in the mixed solvent of glacial acetic acid / anhydrous ethanol / pure water is 7:2; the volume ratio of glacial acetic acid to pure water in the mixed solvent of glacial acetic acid / anhydrous ethanol / pure water is 7:

1.

9. The method for preparing a biodegradable flexible radiation cooling film according to claim 1, characterized in that The mass percentage of ethyl cellulose in the spinning solution described in step 1 is 28%.

10. The method for preparing a biodegradable flexible radiative cooling film according to claim 1, characterized in that In step 2, electrospinning is carried out under the conditions of voltage of 15 kV, injection speed of 0.06 mm / min, temperature of 25°C, humidity of 25%, inner diameter of syringe needle of 0.23 mm, distance between syringe needle and receiving spinner of 25 cm, translation speed of syringe needle of 500 mm / min and rotation speed of receiving spinner of 2 r / min.

Citation Information

Patent Citations

  • Biodegradable infrared emission passive radiation cooling structure and cooling method

    CN109631408A

  • Porous radiation refrigeration film and preparation method thereof

    CN112250973A

  • Spectrum-adjustable radiation refrigeration biomass material and preparation method thereof

    CN115521498A

  • High-tensile electronic fabric with daytime radiation cooling and physiological electric signal monitoring functions as well as preparation method and application of high-tensile electronic fabric

    CN116672152A

  • Cold insulation material as well as preparation method and application thereof

    CN117162608A